2013
DOI: 10.3389/fimmu.2013.00445
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Probiotics and Prebiotics in Inducing Gut Immunity

Abstract: The gut immune system is influenced by many factors, including dietary components and commensal bacteria. Nutrients that affect gut immunity and strategies that restore a healthy gut microbial community by affecting the microbial composition are being developed as new therapeutic approaches to treat several inflammatory diseases. Although probiotics (live microorganisms) and prebiotics (food components) have shown promise as treatments for several diseases in both clinical and animal studies, an understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
140
1
24

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(188 citation statements)
references
References 193 publications
8
140
1
24
Order By: Relevance
“…This evidence that butyrate also has important anti-inflammatory properties highlights the potential of using a carefully selected mixture of probiotic strains and compatible prebiotics (i.e. to formulate synbiotics) to maximize therapeutic efficacy [33].…”
Section: Indirect Effects: 1) Repair Of Hyperpermeable Epithelial Barmentioning
confidence: 99%
“…This evidence that butyrate also has important anti-inflammatory properties highlights the potential of using a carefully selected mixture of probiotic strains and compatible prebiotics (i.e. to formulate synbiotics) to maximize therapeutic efficacy [33].…”
Section: Indirect Effects: 1) Repair Of Hyperpermeable Epithelial Barmentioning
confidence: 99%
“…Prebiotics have most frequently been employed with a view to stimulating the growth of either lactobacilli or bifidobacteria, with many studies focussing on inulin [78][79][80], oligofructose [81,82] or fructooligosaccharides [83,84]. There is a substantial body of evidence linking prebiotic consumption to human health benefits through modulation of the gut microbiota, with research in this area having been the subject of a number of recent reviews [85][86][87]. In one particularly notable recent study, it was observed that supplementing the murine diet with SCFAs or fructooligosaccharides caused a shift in microbiota composition which strongly correlated with beneficial changes in body weight, adiposity and glucose control.…”
Section: Modulation By Dietmentioning
confidence: 99%
“…[33][34][35] When considering the epithelial barrier function, in vitro exposure of reconstituted polarized Caco-2 epithelial cell monolayers to commensal strains either alone or coated with SIgA leads to a completely different pattern of a) cytokine/chemokine secretion, b) pIgR expression, and c) adhesion, indicating that the nature of the bacterium and the association with the antibody results in different sensing by the epithelial cells in the absence of any other partners. 36 While we speculated that commensal bacteria associated with SIgA would have a reduced effect on the reconstituted epithelial layer through mechanisms similar to immune exclusion, it happened that the presence of SIgA increased the bacterial anchoring at the apical surface of IECs.…”
Section: Siga-driven Binding Of Commensal Bacteria To Epithelial Cellmentioning
confidence: 99%